Bridging Theory and Practice: A Qualitative Inquiry into the On-the-Job Training (OJT) Experiences of Hospitality Management Students at West Visayas State University- Lambunao - Aujero-Blanza, Ma. Gerlia; Laman, Mary Jocerie C.; Pelaez, Jyssa C.; Hosenilla, Resanie G. (International Journal of Membrane Science and Technology, 2023)
This research delves into the lived experiences of fourth-year hospitality management students from West Visayas State University-Lambunao during their On-the-Job Training (OJT). Using a phenomenological qualitative methodology, the study sought to uncover the intricate perceptions, emotions, and reflections of the students. Data was primarily gathered through comprehensive semi-structured interviews and was complemented by a review of reflective journals maintained during the OJT period. A purposive sampling approach was chosen, bringing together 25 participants aged between 20-23, ensuring a balanced representation across gender, nature of OJT establishment, and training duration. A thorough thematic analysis of the data highlighted key themes that emerged from the students' OJT experiences. The results offer valuable insights into the challenges and outcomes of OJT, serving as a resource for educators, industry partners, and upcoming hospitality students.